Hadean bridgmanite in the source of a present-day ocean island - Claudine Israel; Catherine Chauvel; Edward Inglis; Hui Chen; Cécile Hébert; James Badro (Nature, 2026)
Abstract Constraining the complex dynamics of the inner Earth unites research efforts across several scientific disciplines, including geochemistry, geophysics and geodynamics. Seismological and geodynamic studies offer insights into the present state of the mantle structure, whereas geochemical approaches characterize its chemical and isotopic heterogeneities 1 , shedding light on the complexity of its evolution. One key challenge is determining the age and origin of its chemical heterogeneities. Here we present new high-precision Nd isotopic measurements in present-day volcanism that identify heterogeneities dating back to the Earth’s earliest history. We report significantly positive 142 Nd anomalies in lavas from the submarine Fani Maoré volcano in the Comoros archipelago. These anomalies require the preservation, in the mantle, of material depleted in light rare-earth elements (REE) and formed within the first 100 million years (Myr) of Earth’s history. We suggest that this material is mainly composed of bridgmanite that crystallized from an early Earth magma ocean. This Hadean bridgmanite may be more widespread in the present-day mantle than previously expected, raising new questions about its survival over billions of years of plate tectonics and vigorous mantle convection.